Partisipasi Masyarakat Pada Pelaksanaan Program Pembangunan dan Pemberdayaan Masyarakat (Probebaya) Terhadap Proses Pembangunan di Kecamatan Sungai Kunjang Kota Samarinda - Muhammad Rachmadani Tarmiji; Daryono; Muhammad Ghiffari Ramadhan Burhan; Mizda Mulyani (Economic Reviews Journal, 2024)
This research aims to find out what form of community participation in the Probebaya program is for development in Sungai Kunjang District, Samarinda City. This research was conducted using a qualitative descriptive method through an observation and interview approach to informants. The Probebaya program, which began in 2021, is a forum for the community to increase participation in development in the City area. Probebaya is a program of the Samarinda City Government to carry out community development activities at the Village level based in the RT area as an effort to realize the ability and independence of the community in infrastructure development, community economic and social improvement. The implementation of Probebaya in the Sungai Kunjang District area runs with high participation from the community, this can all be seen from the level of community participation in the Development Planning Deliberation (Musrenbang) at the Rukun Tetangga (RT) level to the Village Musrenbang level. The community in each Rukun Tetangga (RT) is gathered in a community group called (Pokmas), where this Pokmas will carry out development and community empowerment projects. The participation that is established within the scope of Pokmas can be seen starting from the planning stage, making RAB, implementation to reporting to the utilization of work results. Probebaya is present in order to develop, mobilize and encourage community participation in regional development. The level of community participation from this program is going well with the full support of every element involved, such as the involvement of related agencies and agencies, NGOs, business actors or private parties in the city area, and of course the community who is the subject of this program. The Probebaya program directly has a significant impact on development in the region, especially in areas that have never received financial assistance during the previous Mayor's administration.